KANDUNGAN SIKLAMAT PADA MINUMAN ES CENDOL - Geminsah Putra H Siregar (Poltekkes Kemenkes Medan, 2021)
Cyclamate is an artificial sweetener that is often added to drinks and food. In trade, cyclamate is known by the trade names assugrin, sucaryl, sucrose or sarimanis. The negative effects caused by sodium cyclamate are not immediate, it may have to wait two or thirty years later. The effects include increasing the potential for obesity, dental disorders, learning disorders, emotions, and mental health. testicular wasting and chromosomal damage. The purpose of this study was to determine the presence or absence of cyclamate content in cendol ice. The examination was carried out at the Amami Chemistry Laboratory, Health Polytechnic of the Ministry of Health, Medan, Department of Health Analyst using a qualitative test, namely the color test (deposition) with a total sample of 7 samples taken from cendol ice drink traders. Based on the qualitative test results obtained from 7 samples, 4 positive samples contained cyclamate. By knowing the presence of cyclamate content, it is hoped that producers will use food additives that do not have a negative effect on consumer health. Based on the Minister of Health Regulation No. 033/2012 artificial sweeteners are only intended for low-energy products or for people with diabetes mellitus and not for general let alone especially for children